Company accounts preparation and financial performance of small & medium scale enterprises in Nigeria (Journal of Economic Research & Business Administration, 2021)
The importance of keeping company accounts is to promote the growth evaluate the performance ofsmall and medium scale enterprises (SMEs). Many business entities collapse few years after their incorporationdue to poor management arising from weak accounting structure. This study, therefore, examinesthe relationship between company accounts preparation and the financial performance of SMEs in Nigeria.The study adopts a survey research design. The sample size of 380 respondents was drawn from 20selected SMEs using a purposive sampling technique. Primary data was collected by administering questionnaireto SMEs operators. Multiple Regression model and correlation analysis were employed to analyzethe data. The results of data analysis confirm a strong positive relationship between the companyaccounts preparation and the financial performance of SMEs in Nigeria. This was established from thep-value of 0.00 which is less than 0.01 significant level (0.00 < 0.01). This study concludes that, theadequate company accounts preparation will reflect financial performance of SMEs in Nigeria. This studydiscovers that some SMEs operators in Nigeria hired unskilled accounting personnel making it difficultfor them to prepare reliable annual accounts and reports. This study, therefore, recommends that theSMEs operators in Nigeria should be maintaining proper accounting records of their operations and hireexperienced accounting personnel. Findings from this study will gear up the SMEs operators to appreciatethe need to adequately prepare reliable company accounts that will reflect the financial performanceof their businesses.Key words: Company accounts preparation, financial performance, SMEs.